Analisis Pengaruh Rentabilitas, Solvabilitas dan Likuiditas terhadap Nilai Perusahaan - Silva Nurhasanah; Ekayana Sangkasari Paranita (STIE Widya Manggala, 2019)
This study aims to analyze the effect of profitability ratios, solvency ratios, and liquidity ratios towards firm value of the public companies listed on the Indonesia Stock Exchange in the period 2015-2017. The population is twelve automotive and component subsector companies. Sampling of this study was conducted using purposive sampling technique. Data is in the form of secondary data from each company’s financial statements from the Indonesian Stock Exchange website. The analytical method used is multiple linear regression analysis. The results show that of the ratios that measure the company’s financial performance, only the profitability ratio has a significant positive effect on firm value. The solvency ratio and the liquidity ratio does not significantly influence the firm value. But simultaneously, the three financial ratios show a significant positive effect towards firm value. This research model is quite strong, because all three variables contribute highly in explaining variations in firm value.